Decomposing world income distribution : does the world have a middle class? - Milanović, Branko, 1953- 1953- (Policy research working paper, 2001)
In Asia inequality in income between countries is more important than inequality within countries. In Africa, Latin America, and western Europe and North America, by contrast, there are only small differences between countries; inequality within countries is more important. And when countries are divided in three groups by income level, there is little overlap, very few people in developing countries have incomes in the range of those in the rich countries